A Note on Sharp Embedding Theorems for Holomorphic Classes Based on Lorentz Spaces on A Unit Circle - Shamoyan, Romi; Xu, Wen (Communications in Mathematics and Applications, 2010)
We provide new sharp embedding theorems for holomorphic classes in the unit disk based on Lorentz classes on the unit circle.